The effect of mass treatment with Micotil® at arrival on the health and performance of long-hauled calves - Brazle, F.K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Long-hauled calves (n=170 were either mass-medicated with Micotil® or served as controls. Micotil reduced mortality (1.2 vs 8.1%) and morbidity (59.7 vs 75.5%), but it did not improve ADG.
Keywords: Beef; Stocker calves; Micotil®; Receiving program; Shipping fever; Health